Finite Element Analysis on Wrapping Structure of Piping System - Thurai, Yukeswaran Selva; Tajul Arifin, Ahmad Mubarak (Research Progress in Mechanical and Manufacturing Engineering, 2022)
Abstract: Pipelines system is one of the most important system in the world. Pipeline refer to a long pipe running over distance transporting liquid or gases. Defect in pipe become the critical problem that being faced in various industry. The defected pipeline requires repairs since it will be major problem in transporting liquid or gases. Composite wrapping helps to provide a continuous protective lining that helps save pipelines from the harmful defects. This study focused on wrapping structure and used the Solidworks software to run the simulation analysis. The composite wrapper material that involved in this simulation is CFRP and GFRP. The finite element models were created to simulate all of the tests for the purposes of static analysis. The result revealed that the GFRP material provided high stress than CFRP. Therefore CFRP is the best pipeline wrapper material. The finding in this study is significant as it provides comprehensive understanding of the role and contribution of pipeline composite wrapper to the future of pipeline system repairs. This can serve as an initial step towards optimizing the traditional pipeline system repair by initiating the usage of composite layers wrapping system.